Trimodal processing of complex stimuli in inferior parietal cortex is modality-independent. (June 2021) - Porada, Danja K.; Regenbogen, Christina; Freiherr, Jessica; Seubert, Janina; Lundström, Johan N.
Abstract: In humans, multisensory mechanisms facilitate object processing through integration of sensory signals that match in their temporal and spatial occurrence as well as their meaning. The generalizability of such integration processes across different sensory modalities is, however, to date not well understood. As such, it remains unknown whether there are cerebral areas that process object-related signals independently of the specific senses from which they arise, and whether these areas show different response profiles depending on the number of sensory channels that carry information. To address these questions, we presented participants with dynamic stimuli that simultaneously emitted object-related sensory information via one, two, or three channels (sight, sound, smell) in the MR scanner. By comparing neural activation patterns between various integration processes differing in type and number of stimulated senses, we showed that the left inferior frontal gyrus and areas within the left inferior parietal cortex were engaged independently of the number and type of sensory input streams. Activation in these areas was enhanced during bimodal stimulation, compared to the sum of unimodal activations, and increased even further during trimodal stimulation. Taken together, our findings demonstrate that activation of the inferior parietal cortex during processing and integration of meaningful multisensory stimuli is both modality-independent and modulated by the number of available sensory modalities. This suggests that the processing demand placed on the parietal cortex increases with the number of sensory input streams carrying meaningful information, likely due to the increasing complexity of such stimuli.